Emerging Technologies: Can Artificial Intelligence Enhance Knowledge Management in Arab Universities? - Hussen, Bannaga Taha (JURNAL AL-TANZIM, 2024)
This study aims to identify the implementation of knowledge management processes in Arab universities based on artificial intelligence technology. A phenomenological approach is used to analyze this implementation in leading Saudi Arabian universities. Data were collected through interviews, observations, and literature reviews, then analyzed using the Interpretative Phenomenological Analysis (IPA) method to explore themes and insights from participants' experiences. The study results indicate that implementing knowledge management processes based on artificial intelligence in Arab universities is moderate. Universities have developed networks to generate, store, share, and apply knowledge through artificial intelligence techniques. However, they still face various challenges in this technology-based knowledge management process. Based on these findings, this study recommends improving university infrastructure with the latest artificial intelligence technology and its application in knowledge management. It is also recommended that new services and applications based on artificial intelligence in the field of education be utilized through training programs, workshops, scientific meetings, and seminars related to digital developments. In addition, universities are encouraged to share knowledge internally and externally through knowledge management teams and training units in artificial intelligence systems.